(untitled) (La U Investiga, 2021)
The disease due to the new coronavirus 2019-nCOV (COVID-19), presents with symptoms varied from an upper respiratory catarrh to severe pneumonia or severe acute respiratory syndrome (SARS) due to coronavirus 2 (SARS-CoV-2). There are rare pulmonary complications described, such as spontaneous pneumothorax. Next, we describe the case of a patient with COVID-19 and pneumothorax, who also presented sequelae one year after overcoming the coronavirus infection. The diagnosis, multidisciplinary treatment and follow-up was at the San Luis de Otavalo hospital, establishing a relationship between what is clinically known about pneumothorax and COVID-19, to date, based on the premise that both pathologies are serious and require in principle an individualized treatment adapted to the conditions of each of the patients who manifest it.